Congenital malformations in embryos and neonates of Paslama sea turtle (Lepidochelys olivacea, Eschscholtz, 1829) relocated to nurseries - Gómez-Santana, Alessandro; González-Quiroz, Oscar (La Calera, 2023)
This study collected congenital malformations data in embryos and hatchlings of sea turtle in nests within hatcheries with two forms of incubation (traditional and in sack), in Las Peñitas and Salinas Grandes communities during the nesting season 2019-2020. The sample size was 49 nests per nursery, where newborns were checked immediately and 2 days later the eggs that did not hatch were exhumed. The types of malformations were identified through the comparison of illustrations showing 48 different types of congenital anomalies. The prevalence and intensity of malformations rates were also calculated. A total of 29 types of malformations were identified, distributed among the nurseries as follows: 16 for the Las Peñitas sample and 27 for the Salinas Grandes sample. The most frequent malformations were pigmentation problems and deformations in bone structures, where many of these cases were accompanied by other anomalies in important structures (nose, fins, eyes, etc). The malformation prevalence was 6.9 %, with an intensity of 1.62 malformations per organism in Las Peñitas. meanwhile, congenital abnormalities prevalence was 5.2 % with an intensity of 1.99 malformations per organism in Salinas Grandes. In summary, the malformation prevalence was higher in this study compared to other studies conducted in the region.